Humoral immunity in late‐onset Pre‐eclampsia and linkage with angiogenic and inflammatory markers. (31st August 2018) - Sarween, Nadia; Drayson, Mark T.; Hodson, James; Knox, Ellen M.; Plant, Timothy; Day, Clara J.; Lipkin, Graham W.
Abstract : Problem: Pre‐eclampsia (PE) is a leading cause of maternal and foetal morbidity worldwide. Given the implication of immune mechanisms, we compared markers of humoral immunity in PE and their relationship to circulating markers of inflammation, angiogenic factors, and renal function. Method of study: Serum samples from 88 previously healthy women admitted to hospital with PE and 107 healthy pregnant controls at term were analysed for serum immunoglobulins (Ig), including IgG subclasses and free light chain (sFLC) levels, beta‐2 microglobulin (B2‐M), high‐sensitivity C‐reactive protein (HS‐CRP), albumin, complement proteins (C3 & C4), creatinine, cystatin‐C and the ratio of soluble fms‐like tyrosine kinase‐1 (sFLT‐1) and placental growth factor (PlGF). Results: Compared to the controls, women with PE had significantly reduced renal function, serum IgG (subclass 1 & 3), albumin, and C4 levels, whilst concentrations of total sFLC, HS‐CRP, B2‐M, and sFLT‐1:PlGF were raised. On multivariable analysis, sFLT‐1:PlGF ratio ( P < 0.001), sFLC ( P < 0.001) and IgG1 ( P < 0.024) were found to be independently associated with PE, after accounting for renal function, patient age, BMI, ethnicity, and parity. B2‐M and sFLT‐1:PlGF had comparable diagnostic association with PE ( P = 0.184), and correlated strongly with each other ( ρ = 0.588, P < 0.001) as well as with renal function and adverse clinical outcome. Conclusion: We describe for the first time that PE is independently associated with activation of the humoral immune system independent of deranged kidney function and angiogenic markers. The role of B2‐M as a potential predictive marker of PE remains to be determined. Abstract : Forest plot of the areas under the ROC curves (AUROCs) for those factors which discriminated significantly between PE and control patients. Serum free light chains (FLC) were measured using both the Freelite ® (FL) and monoclonal Luminex (Lx) assays.